Simulação de máquinas supercondutoras de fluxo aprisionado com fitas de segunda geração - Santos, Bárbara Maria Oliveira (2019)
This dissertation presents the first transient finite element simulations of two new topologies of superconducting trapped-flux machines with second generation tapes: one machine with spiral stacks and one, proposed by this work, with double crossed loops. The two computational models used, H and hybrid A-φ-H formulations, are presented and discussed. The implementation of the models is analyzed, as well as the machines work conditions in each simulation. The results obtained in the spiral stack machine are compatible with the experimental data measured in the prototype.